Development of Client-Server System of Remote Access Control to the Premises on the Basis of Mesh-Network - Safonyk, Andrii; Mishchanchuk, Maksym; Kromf, Mykyta; Novruzov, Aydin (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2019)
This article about the system of remote access control to the premises on the basis of Mesh-network. The operating principle of the system and the MESH network are described here. It will also talk about the MESH network and compare it with other network topologies.